Zirconium-boron reactive composite powders prepared by arrested reactive milling. Issue 2 (2nd April 2020) - Hastings, Daniel; Schoenitz, Mirko; Dreizin, Edward L.
ABSTRACT: Zirconium-boron composite powders with the stoichiometric bulk composition corresponding to ZrB2 were prepared using high-energy milling in a shaker mill starting with elemental boron and zirconium. Milling times up to 3 hours were explored. The characterization of the prepared powders included measuring their particle size distribution, crystal structure, and assessment of particle structure and morphology. Reactions in the prepared powders were characterized using thermal analysis as well as custom ignition and combustion experiments. Composite powders consist of a Zr matrix with B inclusions mostly 100 nm or less in size. The homogeneity of mixing between boron and zirconium improves when the milling time increases from 1 to 2 hours; it is not affected by longer milling times. Boron and zirconium start reacting during milling; the degree of this reaction becomes appreciable when the milling time reaches 2 hours. In air, ignition of both pure zirconium and the prepared powders occurs in the same temperature range of ca. 400–700°C for the heating rates varied from 2000 to 20, 000 °C/s. In fuel-rich conditions, ignition of the prepared powders is affected by the reaction between B and Zr, which occurs less readily for powders milled for 2 hours or longer. In air, particles of the prepared composite powders burn faster than either pure boron or zirconium. Flame temperatures for individual composite particles burning in air are reasonably close to those predicted as adiabatic flame temperatures for this composite-air system at stoichiometric and fuel-rich conditions. In combustion products of an air-acetylene flame, the burn rates of the prepared composites are lower than that of zirconium and are comparable to that of boron. Powders prepared by 1-hour milling burn faster than powders prepared using longer milling times.